The microbes fight back : antibiotic resistance - Bowater, Laura (Royal Society of Chemistry, 2017)
Antibiotics are familiar drugs to us all, so familiar that we may take them for granted. They allow us to survive life-threatening infections, and allow us to protect the animals we farm for food. Many antibiotics have now become ineffective against common diseases, and there are few alternative treatments to replace them. In this topical book, Laura Bowater, Professor of Microbiology Education and Engagement at Norwich Medical School, considers the past, present and uncertain future of antibiotics. This book begins by looking back at how infectious diseases, such as smallpox and The Plague, were able to wreak havoc on populations before the discovery of the first antibiotics. These then revolutionised the medical world. In an engaging and accessible style, Professor Bowater takes the reader through how antibiotics are made, how bacteria are able to mutate and develop resistance and she explains why there is now a lack of new antibiotic drugs coming to market. What will a future of continued antibiotic resistance look like? How can human activities prevent the rise of 'superbugs'? Professor Bowater highlights the need for universal cooperation in order to tackle this global health challenge, which, if not addressed, could transport us back to the medical dark ages. -- Provided by publisher.